Effective utilisation of waste cement concrete dust in bituminous concrete - Choudhary J.; Asthana G.; Sukhija M.; Wagh V.P.; Gupta C. (My University, 2025)
The suitability of waste cement concrete dust (CD) and conventional hydrated lime (HL) as fillers in bituminous concrete was investigated. Bituminous mixes containing CD or HL in different proportions were designed. Their performance was studied using the Marshall quotient, indirect tensile strength, tensile strength ratio (TSR), passive and active adhesion and Cantabro tests. The cost of the various mixes and their greenhouse gas (GHG) emissions were also compared. Finally, the optimum filler content for both mixes was determined. The mixes containing CD displayed rutting, cracking and ravelling resistance similar to those of conventional mixes. CD offered improved affinity towards bitumen and ensured excellent moisture resistance (TSR%). Compared with a traditional mix (4% HL), the use of CD marginally lowered the cost by around 3-8% and reduced the GHG emissions by more than 50%. Overall, the addition of CD ensured satisfactory engineering performance at a relatively lower cost and significantly lower GHG emissions. © 2024 Emerald Publishing Limited: All rights reserved.